Strain‐Activated Copper Catalyst for pH‐Universal Hydrogen Evolution Reaction - Kang, Wen‐Jing; Feng, Yi; Li, Zhe; Yang, Wen‐Qi; Cheng, Chuan‐Qi; Shi, Zi‐Zheng; Yin, Peng‐Fei; Shen, Gu‐Rong; Yang, Jing; Dong, Cun‐Ku; Liu, Hui; Ye, Fu‐Xing; et al. (Advanced functional materials, 2022)
Developing low‐cost and high‐activity pH‐universal hydrogen evolution reaction (HER) catalysts is very crucial to the industrialization of water electrolysis. However, the high price, low yield, and poor stability of current HER catalysts make them difficult to meet practical requirements. Herein, a plasma spraying technique is employed to prepare self‐supported Cu catalysts with tensile strain for the first time. The tensile strain upshifts the d‐band of Cu, improves the water dissociation and H* adsorption, eventually improves the intrinsic HER catalytic activity. As such, Cu electrode achieves overpotentials of 182 mV in 0.5 m H2SO4, 261 mV in 1 M PBS, and 121 mV in 1 M KOH at 10 mA cm–2. In addition, Cu electrode also performs well at high current densities, the overpotentials at 1 A cm–2 are much lower than those of Pt foil in acid, neutral, and alkaline solutions. The Cu electrode prepared by plasma spraying exhibits an excellent pH‐universal HER catalytic activity, superb long‐term stability, and marvelous corrosion resistance. The superb HER activity is attributed to self‐supported porous structure, abundant active sites, tensile strain enhanced intrinsic catalytic activity, and small charge transfer resistance.